Dwumianowy model wyceny rzeczowej opcji złożonej - Rudny, Włodzimierz (Binominal Model of Valuation of a Compound Real Option, 2007)
Real options analysis is considered by numerous researchers as an extension or alternative to discounted cash flow methods of investment project evaluation. As regards the models of real option valuation, binominal model is ranked among the most popular, mainly due to its simplicity, functionality and clarity which allow to visualize the process of option valuation. The article discusses the key issues of compound option valuation using the binominal model based on the data of hypothetical investment project. Real option analysis is compared with DCF based valuation methods. The article also provides some comments concerning the reasons for limited application of real option analysis in practice
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 328-337